Monetarism and Monetary Economics A Delayed Comment - Helmut Frisch (Kredit und Kapital, 1977)
Monetarismus und monetäre ökonomische Theorie Prof. Mayer hat in seinem Essay "The Structure of Monetarism" den gegenwärtigen "Monetarismus" durch 12 Propositionen charakterisiert. Der vorliegende Beitrag befaßt sich im wesentlichen mit der Neuformulierung der Quantitätstheorie (Proposition I in Prof. Mayers Darstellung), sowıe mit dem "Stabilitätspostulat" der Monetaristen. Die Neo-Quantitätstheorie kommt in dem Akzelerationstheorem zum Ausdruck, wonach eine Beschleunigung im Wachstum der Geldmenge reale Effekte erzeugt, während im steady state die Rate des Geldmengenwachstums nur die Inflationsrate bestimmt. Es wird gezeigt, daß das Akzelerationstheorem adaptive Erwartungen impliziert; rationale Erwartungen würden reale Effekte bei einer Änderung des Geldangebots von vornherein ausschalten. Empirische Untersuchungen in den USA zeigen, daß nach dem II. Weltkrieg die Akzeleration oder Dezeleration der Geldmenge regelmäßig nicht antizipiert wurde, so daß das Akzelerationstheorem eher mit der empirischen Evidenz kompatibel erscheint als rationale Erwartungen. Der fundamentale Unterschied zwischen Monetarismus und monetärer Ökonomie liegt in der Annahme oder Ablehnung des "Stabilitätspostulates", wonach die Marktwirtschaft inhärent stabil sei. Monetarismus wird definiert als monetäre ökonomische Theorie mit der zusätzlichen Annahme des "Stabilitätspostulates". Dieses Konzept hat keinen operationalen Charakter und gehört eher zur "Weltanschauung" der monetaristischen Richtung. Ältere "Monetaristen" wie K. Wicksell und F. A. Hayek verwendeten anstait des Stabilitätspostulates das Konzept des Kumulativen Prozesses, welcher impliziert, daß der monetäre Sektor inhärent instabil sei. – – Monetarism and Monetary Economics In his essay "The Structure of Monetarism" Prof. Mayer has characterized present-day monetarism by using 12 propositions. In this note I concentrate on his first proposition (the Neo-quantity theory of money) and on the "stability"'- postulate. The Neo-quantity theory is discussed by appeal to the so called accelerations-theorem, according to which an acceleration (or deceleration) of the rate of growth of money supply generates real effects, while in a steady state the rate of money supply determines only the rate of inflation. The few empirical studies make it questionable, whether one can speak of a "predominance" of a monetary impulse on output and production. It is contended that the accelerations theorem is compatible with adaptive expectations but not with the model of rational expectations. According to the latter a monetary impulse would only generate inflationary an no real effects. Recent empirical investigations convey the impression that for the USA in the period after the II. World War the acceleration or deceleration of the rate of money expansion has not been anticipated. Therefore the accelerations theorem seems to be more compatible with the empirical evidence than does the model of rational expectations. The fundamental difference between monetarism and monetary economics in general is to be found in the "stability conjecture" according to which the private sector of the economy is inherently stable. "Monetarism" is defined as monetary economics with the additional assumption of the "stability conjecture". This conjecture is not an operational concept and belongs to the "Weltanschauung" of tne monetarist school of thought. After a discussion of a more operational concept of stability it is pointed out that older monetarists such as Wicksell and Hayek used instead of the stability conjecture the concept of the "cumulative" process, which implies that the monetary sector of the economy is inherently unstable.
Keywords: 330